2021
DOI: 10.3389/fmicb.2021.615924
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae Type 1 Pilus – A Multifunctional Tool for Optimized Host Interaction

Abstract: Streptococcus pneumoniae represents a major Gram-positive human pathogen causing bacterial pneumonia, otitis media, meningitis, and other invasive diseases. Several pneumococcal isolates show increasing resistance rates against antibacterial agents. A variety of virulence factors promote pneumococcal pathogenicity with varying importance in different stages of host infection. Virulence related hair-like structures (“pili”) are complex, surface located protein arrays supporting proper host interaction. In the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 77 publications
1
13
0
Order By: Relevance
“…We further confirmed a possible binding specificity for galactose and fucose (greater with the former than the latter) in the D2 (vWFA) domain via glycan microarray screening. Here, it is worth mentioning that the RrgA tip pilin was shown to bind various glycans, including galactose [61,62]. Remarkably, we were able to show and validate that the PitA tip pilin (via the PI-2 pilus) forms an interaction with the CafA tip pilin (via the type 2 pilus) during the coaggregation of S. oralis and A. oris cells.…”
Section: Discussionsupporting
confidence: 65%
“…We further confirmed a possible binding specificity for galactose and fucose (greater with the former than the latter) in the D2 (vWFA) domain via glycan microarray screening. Here, it is worth mentioning that the RrgA tip pilin was shown to bind various glycans, including galactose [61,62]. Remarkably, we were able to show and validate that the PitA tip pilin (via the PI-2 pilus) forms an interaction with the CafA tip pilin (via the type 2 pilus) during the coaggregation of S. oralis and A. oris cells.…”
Section: Discussionsupporting
confidence: 65%
“…87 Most streptococcal cell surface proteins possess a cell wall-anchored motif (typically Leu-Pro-x-Thr-Gly [LPxTG]) in the C-terminal regions. [88][89][90] Sortases are transpeptidases that catalyze the attachment of proteins covalently to cell wall components via the LPxTG motif. [88][89][90] This type of enzymes also catalyzes the assembly of pilus subunits into pili, long filamentous structures with a pilus polymer backbone (see the next section).…”
Section: Cell Surface Proteins and Enzymes (1): Matrix-binding Proteinsmentioning
confidence: 99%
“…Pili of these streptococci consist of a pilus major backbone subunit, with one or more minor pilus subunits that are covalently assembled on the cell surface by the action of pilus-associated sortases. 45,46,88,90 The pilus islets in the genomes of these streptococci are composed of genes encoding multiple pilus subunits carrying the LPxTG motif together with genes for sortases. 45,46,[88][89][90] The pili of pathogenic streptococci serve as adhesins in host cells.…”
Section: Cell Surface Proteins and Enzymes (2): Pilimentioning
confidence: 99%
See 1 more Smart Citation
“…Two types of pili have been identified in S. pneumoniae : type 1 encoded by Pilus Islet 1 (PI-1) [ 4 , 11 ] and type 2 encoded by Pilus Islet 2 (PI-2) [ 12 ]. Both pili are polymers of major- and minor-pilus proteins covalently linked and anchored to the cell surface [ 13 ]. Molecular epidemiology studies showed that only a small proportion of the pneumococcal population harbors pili-encoding genes in their genomes.…”
Section: Introductionmentioning
confidence: 99%